Bima Traditional House Ethnobotany: Uma Lengge - Nurhajratul Yusmerianti; Khairuddin Khairuddin; I Gde Mertha (Postgraduate, University of Mataram, 2023)
Ethnobotany is a science that explains the knowledge of traditional communities on the use of plants to support their lives. One of the uses of plants for traditional building materials can be seen in the Uma Lengge building which is a traditional building located in the Wawo District, Bima Regency, West Nusa Tenggara. This building used to function as a residence for the Mbojo tribe. However, along with the development of the times, the function of the building has been transferred only as a place to store rice. This research aims to analyze the types of constituent plants and explore information about the local wisdom contained in Uma Lengge's architecture. This research type is qualitative using descriptive methods and plant anatomy approaches. Data collection is done using observations, interviews, and documentation. The selection of informants used the snowball sampling method. Based on the results of the study 7 types of plants were used as constituents for the construction of traditional Uma Lengge houses in Maria Village, teak (Tectona grandis Lf.), areca nut (Areca catechu L.), coconut (Cocos nucifera L.), banyan (Ficus benjamina L.), bamboo (Gigantochloa atter Kurz.), hibiscus (Hibiscus tiliaceus L.), and ndolo (Imperata confera (J.Presl) Ohwi). The local wisdom contained in Uma Lengge architecture is still being applied by the people of Maria Village for generations which include customs, and the preservation of annual traditions or rituals that have good values ​​to be passed down